The Removal of Cu (II) and Pb (II) on Wastewater using Microbial Fuel Cells (MFCs) with Graphite/Chitosan Electrode - Adhi Satriyatama; Nadia Winda Damaranti (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2020)
Heavy metal contamination in water has become a major problem in the environment as a result of very rapid industrial development. The presence of heavy metal contamination is becoming toxic, carcinogenic, and able to harm living organisms in ecosystem. Various methods have been applied for reducing heavy metals in water with high efficiency results, but most of them are still require complicated equipment and procedure. Microbial Fuel Cell (MFC) is a new technology for reducing heavy metals using biosorption activity of microorganisms. This study aimed at analyze the concentrations reduction of Cu (II) and Pb (II) using MFC on river sediments and sludge substrate. At the initial stages, graphite/chitosan electrodes were prepared and characterized. Subsequently, the exoelectrogenic microorganisms in the substrate were identified by the Gram staining method and biochemical tests. The processes were carried out in MFC dual chamber reactor with open circuit system for 120 hours. Heavy metal concentrations were analyzed using Atomic Absorption Spectrometry (AAS) periodically at wavelengths 250 nm (Cu) and 283 nm (Pb). COD (Chemical Oxygen Demand) removal, power density, DO (Dissolved Oxygen), and pH were also analyzed. The concentration of Cu (II) metal experienced the biggest decrease in wetland mud substrate that was 75%, followed by Pb (II) which was 45%. Whereas on the river sediment substrate, the concentration of Pb (II) experienced the largest decrease of 81%, followed by Cu (II) of 67%. In addition, measurements of power density values on both substrates were tend to be fluctuated.